Ultraviolet photofragmentation spectroscopy of metal dication sandwich complexes in the gas phase combined with DFT/TDDFT calculations - Ma, Lifu (2013)
Metal dication-ligand sandwich complexes have attracted intense attention recently for their widely use in catalysis, biochemistry and material science. The experimental techniques developed by our group have allowed forming, confining, cooling and investigating a wide range of metal dication complexes in the gas phase. In this thesis, the ultraviolet photofragmentation studies of Pb(II), Cu(II) and Ca(II) sandwich complexes with aromatic ligands are performed using a hybrid quadrupole ion trap instrument, followed by DFT/TDDFT calculations. The experimental results indicate that the complexes are capable of yielding structured, sometimes conformation resolved, UV spectra. The spectra of metal dication-benzene complexes exhibit features in the wavelength range 220-270 nm and a big raise as the wavelength decreases. The lead dication-bis(toluene) complex spectrum shows some well-resolved features arising from different conformers. The theory suggests that all of these complexes have excitations including significant contributions from the metal-based orbital. The adiabatic TDDFT methodology is able to give reasonable agreement between the calculated excitations and the experimental spectra for the close-shell complexes. But for some open-shell complexes, the calculated excitations are spin contaminated, which need to be discarded or corrected in the future. The degree of spin contamination for selected excitations is qualified by calculating the <S2> values. For lead and calcium open-shell complexes, most of the excitations that can match the experimental features can be trusted. However, for the copper open-shell complex, only three states are ~90% doublet in their character which are responsible for some excitations that can match the spectra. Challenges such as developing the theory to describe the open-shell system and refining the experimental techniques to improve the resolution of the spectra, still remain.